Can Public Works Programs Reduce Youth Crime? : Evidence from Papua New Guinea's Urban Youth Employment Project - Ivaschenko, Oleksiy; Naidoo, Darian; Newhouse, David; Sultan, Sonya (World Bank, Washington, DC, 2017)
Crime rates in Papua New Guinea's capital city of Port Moresby are among the highest in the world. Few youth work, and good jobs are scarce. In 2013, the National Capital District Commission partnered with the World Bank to implement the Urban Youth Employment Project. The project offers out-of-school and out-of-work youth two months of public works employment or, for academically qualified candidates, six months of classroom and on-the-job training. This paper presents difference-in-difference estimates of project impacts on participants' social and criminal behavior, 12 to 18 months after completion. The control group consists of observably similar youth living in areas not served by the program. Project participants became less likely to hang out with friends at night, have a best friend involved in crime, and have friends involved in fights or robberies. The program also increased subsequent employment rates, and significantly reduced aggressive behavior and gratuitous property damage. However, there is little robust evidence that the program reduced participants' engagement in or exposure to crime. The study concludes that the program had strong and healthy effects on participants' peer group and behavior, but more limited effects on the socioeconomic causes of crime.